Association of ABO Blood group phenotypes with FEV1/FVC values among students of Aziz Fatima Medical and Dental College - Hira Zahid; Anam Rehman; Saima Zareen; Sana Rasheed; Shireen Jawed; Benash Altaf (Journal of Rawalpindi Medical College)
Objective: To find the frequency of obstructive and restrictive lung disease in various blood groups in young students of Aziz Fatimah Medical and dental college.